Unravelling the Link Between Financialisation and Economic Growth: Evidence from Croatia - Agim Mamuti; Fatbardha Kadiu; Idaver Sherifi; Inna Romānova; Simon Grima (Risks)
This study investigates the relationship between financialisation and economic growth in Croatia, focusing on the period from 1995 to 2021. Using time series econometric models, including the Augmented Dickey–Fuller test for stationarity, Johansen’s cointegration test for long-term relationships, and the Granger causality test within the Vector Error Correction Model (VECM) framework, the research reveals a sustained long-term equilibrium relationship between financialisation and economic growth in Croatia. However, the Granger causality test does not indicate a definitive causal direction between these variables. While the study is limited to the Croatian context and the specified period, its findings have significant implications for policymakers in Croatia and similar emerging markets. These results suggest that while financialisation can enhance economic growth through better resource allocation and increased investment, it may also pose risks such as financial instability. Such measures aim to mitigate the risks associated with financialisation while promoting sustainable economic growth. To address these challenges, we recommend the implementation of robust regulatory frameworks, financial literacy initiatives, and economic diversification strategies. Such measures aim to mitigate the risks associated with financialisation while promoting sustainable economic growth. The study fills an important research gap on financialisation in emerging markets, particularly in Croatia, providing empirical evidence on the long-term relationship between financialisation and economic growth and highlighting the need for context-specific policy interventions.